Strategies for Instilling Religious Moderation Through Traditional Games for Elementary School Children - Abdul Khobir; Arkan Abdul Ghoni; Fidiyah Sari; Muhammad Maskur Musa (Edukasia Islamika : Jurnal Pendidikan Islam, 2023)
The cultivation of religious moderation needs to be done considering the increasingly extreme differences, so it is necessary to form an attitude that can deal with such things. Religious moderation needs to be implemented for Madrasah Ibtidaiyah students because they are very vulnerable to deviant behavior. Educators have made efforts to instill moderation values through several strategies that have been designed. This strategy is a surefire way to provide a stimulus for religious moderation, starting from traditional, free, reflective, and transinternalization strategies. This study aims to describe the inculcation strategy regarding religious moderation and discover the implications of instilling religious moderation through traditional hopscotch games for Madrasah Ibtidaiyah children. The method used in this research is field qualitative, which involves analyzing data obtained from observations, interviews, and documentation during the study at an elementary-level educational institution, namely MI Sullam Taufiq. The results of this study indicate that the development of religious moderation owned by students through learning with the application of traditional crank games is more concrete to facilitate understanding and application of religious moderation in students.